ANALISIS PERUBAHAN KEBIJAKAN LUAR NEGERI IRAN TERHADAP ISRAEL PASCA SERANGAN 7 OKTOBER 2023 - Dharmawan Ajie Laksono, Satria; Fadhil Rahman, Nazhmi; Ainur Fitri, Rahmania; Abizzar Maulana, Muchammad; Dwi Hapsari, Renitha; Wibowo, Prihandono (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research analyses the transformation of Iran’s foreign policy towards Israel following the Hamas attack on 7 October 2023. The event triggered an escalation that shifted the long-standing proxy warfare into direct confrontation between Iran and Israel. For decades, Iran has supported Palestinian resistance groups and the broader axis of resistance, while avoiding direct military involvement. However, Israel’s attacks on Iranian assets and senior officials, particularly the strike on Damascus in April 2024, created structural pressures that compelled Iran to retaliate through open military operations, such as Operation True Promise I–III. This study employs a qualitative explanatory method, applying Joakim Eidenfalk’s theory of foreign policy change, which highlights domestic factors (public opinion, media, interest groups, political parties, and bureaucracy) alongside international factors (global, regional, bilateral, and non-state actors). The concept of windows of opportunity is used to explain how structural conditions provide critical moments for Iranian decision-makers to alter foreign policy. The findings reveal that the change constitutes a restructuring process, marked by the shift from proxy warfare to open confrontation. This transformation reflects Iran’s effort to reinforce its regional position, consolidate domestic legitimacy, and demonstrate its military capacity in countering Israel.